Reducing child wasting through integrated prevention and treatment in Mali - Huybregts, Lieven; Diop, Loty; Diatta, Ampa Dogui; Fall, Talla; Ouedraogo, Moctar; Barba, Francisco; Sawadogo, Abdoulaye; Becquey, Elodie (International Food Policy Research Institute, 2023)
Wasting is a persistent public health problem affecting 45.4 million children under five years of age worldwide. Wasting is responsible for the deaths of 875,000 children under the age of five every year. Children who survive often suffer long-term damage to their cognitive and physical development. Member countries of the World Health Assembly (WHA) have agreed to reduce and maintain the prevalence of wasting to less than 5 percent by 2025. Despite the commitment to tackle wasting, however, only one country in West Africa is on course to meet the WHA target. In contrast, seven countries, including Mali, have made no progress or have a worsening situation. In Mali, estimates from 2020 show prevalence levels of 9.3 percent, with critical regional disparities. Existing programs that aim to prevent or treat child wasting exist but typically suffer from low coverage and tend to be poorly integrated. While both strengthened prevention and treatment of wasting hold the potential to impact child wasting, substantial synergies can be expected when prevention is integrated with screening, referral, and treatment services. Such integration should happen at the community level to maximize the accessibility of services for caregivers and their children. Since the introduction of Mali's national infant and young child feeding strategy in 2012 (Ministère de la Santé du Mali 2012), community care groups called Nutrition Action Support Groups (NASGs) have taken center stage in delivering preventive behavior change communication (BCC) on infant and young child feeding (IYCF) practices and child health. However, to leverage the impact of these efforts on child wasting, NASG services need to be extended to support existing community-based treatment services and to prevent any posttreatment relapse. Further evidence is needed on the coverage and quality of implementation of these community groups, as existing evidence is scarce.